2001
DOI: 10.1086/321547
|View full text |Cite
|
Sign up to set email alerts
|

The Limiting Effects of Dust in Brown Dwarf Model Atmospheres

Abstract: We present opacity sampling model atmospheres, synthetic spectra and colors for brown dwarfs and very low mass stars in two limiting case of dust grain formation: 1) inefficient gravitational settling i.e. the dust is distributed according to the chemical equilibrium predictions, 2) efficient gravitational settling i.e. the dust forms and depletes refractory elements from the gas, but their opacity does not affect the thermal structure. The models include the formation of over 600 gas phase species, and 1000 l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
1,373
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 972 publications
(1,416 citation statements)
references
References 93 publications
(108 reference statements)
40
1,373
2
1
Order By: Relevance
“…Liu et al 2013b) to best fit model atmospheres (Allard et al 2001(Allard et al , 2012, as determined from χ 2 minimization. Since PSO J318.5−22 has a known distance, the scaling factor needed to match the flux level of the model to the observed spectrum (= R 2 /d 2 where R is the radius and d is the distance) provides an estimate of PSO J318.5−22's radius.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al 2013b) to best fit model atmospheres (Allard et al 2001(Allard et al , 2012, as determined from χ 2 minimization. Since PSO J318.5−22 has a known distance, the scaling factor needed to match the flux level of the model to the observed spectrum (= R 2 /d 2 where R is the radius and d is the distance) provides an estimate of PSO J318.5−22's radius.…”
Section: Resultsmentioning
confidence: 99%
“…doublet, the inclusion of the potassium modern3 line profile is important for this work since sodium and potassium resonance lines form the pseudo continuum in the optical range. We present only synthetic spectra calculated using the "GAIA-cond" model setup (Allard et al 2001) in order to demonstrate the influence of the line profiles in the synthetic spectra. The "GAIA-cond" approximations consider fully "rained-out" condensed dust in chemical equilibrium, see Allard et al (2001) for details.…”
Section: Profilesmentioning
confidence: 99%
“…We present only synthetic spectra calculated using the "GAIA-cond" model setup (Allard et al 2001) in order to demonstrate the influence of the line profiles in the synthetic spectra. The "GAIA-cond" approximations consider fully "rained-out" condensed dust in chemical equilibrium, see Allard et al (2001) for details. For each line profile setup, a model atmosphere has been calculated and converged before generating the synthetic spectrum.…”
Section: Profilesmentioning
confidence: 99%
“…Since this contrast is more favorable at near-IR and Infrared wavelengths, caracterisation studies of planetary candidates found by imaging use model atmospheres ignoring the effects of impinging radiation on the shape of their SED, and account for stellar irradiation by applying an achromatic correction factor. These models (in Allard et al 2001) are readily available via a web simulator (http://phoenix.ens-lyon.fr/simulator), and tested for the study of brown dwarfs which cover a similar range of parameters (Teff, surface gravity) than for young planetary mass objects.While the study of brown dwarfs can be enlightening for the study of planetary atmospheres -brown dwarf atmospheres are the site of an onset of dust cloud formation, strong rotation, and/or magnetic fields -their study thus far proceeded using only 1D static, often plane-parallel model atmospheres of various degrees of radiative transfer sophistication: Opacity Sampling vs. K-coefficient techniques, NLTE, photoionisation and photochemistry vs. Equilibrium Chemistry, stationary particle diffusion solutions, cloud models, assuming adiabaticity instead of using the Mixing Length Theory for convective mixing, etc.For instance, Barman, Hauschildt & Allard (2001), Barman et al (2002), andAllard (2005) have explored the impact of dust cloud formation, NLTE and the photoionisation of sodium, and a reconstruction of the planetary surface with 1D static models, using the (at depth) entropy matching technique often used in a similar way for the study of binary stars in astrophysics. This technique allows to explore the orbital phase variations of the SED.…”
mentioning
confidence: 99%
“…Since this contrast is more favorable at near-IR and Infrared wavelengths, caracterisation studies of planetary candidates found by imaging use model atmospheres ignoring the effects of impinging radiation on the shape of their SED, and account for stellar irradiation by applying an achromatic correction factor. These models (in Allard et al 2001) are readily available via a web simulator (http://phoenix.ens-lyon.fr/simulator), and tested for the study of brown dwarfs which cover a similar range of parameters (Teff, surface gravity) than for young planetary mass objects.…”
mentioning
confidence: 99%